UNIT 3.9 Computational Large‐Scale Mapping of Protein‐Protein Interactions Using Structural Complexes. Issue 1 (24th September 2013) - Shoemaker, Benjamin; Wuchty, Stefan; Panchenko, Anna R.
Abstract: Although the identification of protein interactions by high‐throughput methods progresses at a fast pace, "interactome" datasets still suffer from high rates of false positives and low coverage. To map the interactome of any organism, this unit presents a computational framework to predict protein‐protein or gene‐gene interactions utilizing experimentally determined evidence of structural complexes, atomic details of binding interfaces and evolutionary conservation. Curr. Protoc. Protein Sci . 73:3.9.1‐3.9.9. © 2013 by John Wiley & Sons, Inc.